Muscle ring finger protein-1 inhibits PKCε activation and prevents cardiomyocyte hypertrophy - Arya, Ranjana (The Rockefeller University Press, 2004)
Much effort has focused on characterizing the signal transduction cascades that are associated with cardiac hypertrophy. In spite of this, we still know little about the mechanisms that inhibit hypertrophic growth. We define a novel anti-hypertrophic signaling pathway regulated by muscle ring finger protein-1 (MURF1) that inhibits the agonist-stimulated PKC-mediated signaling response in neonatal rat ventricular myocytes. MURF1 interacts with receptor for activated protein kinase C (RACK1) and colocalizes with RACK1 after activation with phenylephrine or PMA. Coincident with this agonist-stimulated interaction, MURF1 blocks PKCε translocation to focal adhesions, which is a critical event in the hypertrophic signaling cascade. MURF1 inhibits focal adhesion formation, and the activity of downstream effector ERK1/2 is also inhibited in the presence of MURF1. MURF1 inhibits phenylephrine-induced (but not IGF-1–induced) increases in cell size. These findings establish that MURF1 is a key regulator of the PKC-dependent hypertrophic response and can blunt cardiomyocyte hypertrophy, which may have important implications in the pathophysiology of clinical cardiac hypertrophy.